Evaluasi Pengendalian Intern Persediaan Pipa Distribusi Dan Accessories Dalam Mengamankan Asset Perusahaan Pada PDAM Tirta Pakuan - Hasibuan, David; Setiawan, Hendra (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2012)
Internal Control System is an organization structure including all coordinated ways and actions to safeguard companyâs assets, to maintain the accuracy of accounting data and other data, in order to ensure the reliability of reports, efficiency and affectiveness are able to increase, and loyalty to the managementâs policy can be secured.By conducting Internal Control System, it can be managed all companyâs assets and supplies properly with the relult that the real condition is appropriate with the accounting. The purpose of this study is to evaluate whether internal control system to secure companyâs assets and supplies has been carried out properly and in accordance with the generally accepted in Indonesia in accordance with procedures issued by the company. The study was conducted at PDAM Tirta Pakuan Bogor. PDAM is a company operating in processing of drinking water, the biggest producer in Bogor. The result of this study shows that PDAM Tirta Pakuan Bogor has done internal control well to secure the companyâs assets.The control is quite justifiable to serve as the basis for decision making as presented in the balance sheet. And itâs done because each of stock supplies has its respective function and the existing inventories are used to meet cutomersâ needs, so that the existing stock will be sufficient and there is no over stock. The result of the evaluation in this study shows that supplies in warehouse is in accordance with the needs and storage is carried out by separating types, quality, and size, so that if it must be inventories checking anytime, it can be carried out easily. Thereby, the existing supplies can be maintained properely and protected from any loss.